Strengthening Defense Industries in Developing Countries Through Defense Diplomacy: A Comparative Study of Indonesia and the Philippines - Akmal Nugraha, Deja; Inkiriwang, Frega Wenas; Banyu Perwita, Anak Agung (CV RIFAINSTITUT, 2024)
This study investigates the role of defense diplomacy in strengthening defense industries in developing countries, focusing on Indonesia and the Philippines. Defense diplomacy, defined as the use of diplomatic measures to achieve national security objectives, has become a strategic tool for developing countries to enhance their defense capabilities. Through a comparative case study, this research examines the defense diplomacy strategies of Indonesia and the Philippines, exploring their initiatives, partnerships, and outcomes in defense industry development. The results show that both countries have effectively utilized defense diplomacy to advance their defense industries, though with differing strategic focuses. Indonesia's regional security approach and defense manufacturing efforts contrast with the Philippines' targeted maritime security enhancements and joint training initiatives. The study underscores the importance of defense diplomacy in developing national defense capabilities and its potential to significantly contribute to defense industry development in developing countries, offering valuable insights for policymakers and scholars in international relations and defense policy